Returns to Human Capital under the Communist Wage Grid and During the Transition to a Market Economy - Katherine Terrell; Jan Svejnar; Daniel Münich (Institute for the Study of Labor (IZA), 2000)
Under communism, workers had their wages set according to a centrally-determined wage grid. In this paper we use new micro data on men to estimate returns to human capital under the communist wage grid and during the transition to a market economy. We use data from the Czech Republic because it is a leading transition economy in which the communist grid remained intact until the very end of the communist regime. We demonstrate that for decades the communist wage grid maintained extremely low rate of return on education, but that the return increased dramatically and equally in all ownership categories of firms during the transition. Our estimates also indicate that men?s wage-experience profile was concave in both regimes and on average it did not change from the communist to the transition period. However, the de novo private firms display a more concave profile than SOEs and public administration. Contrary to earlier studies, we show that men?s inter-industry wage structure changed substantially between 1989 and 1996.
Keywords: P2; J3; J4; 330; Communism; Czech Republic; human capital; labor; retrospective data; transition; wages; Bildungsertrag; Humankapital; Lohnstruktur; Planwirtschaft; Uebergangswirtschaft; Tschechoslowakei; Tschechische Republik